PENGARUH KOPERASI TERHADAP USAHA MIKRO KECIL MENENGAH (STUDI KASUS : PENYALURAN MODAL PEMBIAYAAN PT XX DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT REGIONAL KEDIRI) - putri rachmawati; Albert Gamot Malau (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the community's economy. This study aims to analyze the distribution mechanism and effectiveness of financing provided by the PNM Mekaar Kediri Branch in improving community economic welfare, as well as identifying factors influencing the success of customers' micro-enterprises. The results of this study are expected to provide theoretical benefits as a reference for the development of economics, particularly regarding microfinance management efforts, and to benefit PNM Mekaar in improving the quality of its services and empowerment programs. The method used in this study was a qualitative approach, conducting several interviews with active PNM Mekaar customers in the follow-up cycle. Data analysis was conducted through the stages of data presentation and drawing conclusions to obtain an overview of changes in the community's economic and social conditions before and after receiving financing. The results indicate that capital loans from PNM Mekaar have a positive impact on improving community welfare. Economically, customers are able to develop their businesses and increase their income. However, there are some obstacles in repaying installments during business downturns. Overall, this program has proven to be effective in supporting community economic empowerment.